Proceedings of 2nd International Multi-Disciplinary Conference Theme: Integrated Sciences and Technologies, IMDC-IST 2021, 7-9 2022
DOI: 10.4108/eai.7-9-2021.2315497
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating effect of Alteplase in bleomycin-induced pulmonary fibrosis in adult rats

Abstract: The goal of this study was to see if alteplase may help adult rats suffering from bleomycin-induced lung fibrosis. Alteplase 0.9mg/ kg i.p. as a single dose daily for 3weeks, significantly ameliorated the declined serum levels of SOD and GSHpx, and significantly, decrease the elevated level of hydroxyproline in (BLM) treated rats. The bulk of the alveolar walls were filled by collagenous fibres with diffuse cellular infiltration, bands of collagen fibres, and increased macrophages and fibroblast cells in secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…A recent study has confirmed the efficacy and safety of Alt in the treatment of moderate/severe COVID-19-induced acute respiratory distress syndrome. In addition, it has been found to decrease pulmonary fibrosis in rat models induced by bleomycin and increase levels of antioxidants while reducing hydroxyproline [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has confirmed the efficacy and safety of Alt in the treatment of moderate/severe COVID-19-induced acute respiratory distress syndrome. In addition, it has been found to decrease pulmonary fibrosis in rat models induced by bleomycin and increase levels of antioxidants while reducing hydroxyproline [ 32 ].…”
Section: Introductionmentioning
confidence: 99%